Monocentric observational cohort study to investigate the transmission of third-generation cephalosporin-resistant Enterobacterales in a neonatal intensive care unit in Heidelberg, Germany - Nurjadi, Dennis; Eichel, Vanessa; Pöschl, Johannes; Gille, Christian; Kranig, Simon A.; Heeg, Klaus; Boutin, Sébastien (Microbiology spectrum, 2023)
Third-generation cephalosporin-resistant Enterobacterales is a major threat for newborns in neonatal intensive care units (NICUs). The route of acquisition in a non-outbreak setting should be investigated to implement adequate infection prevention measures. To identify risk factors for colonization with and to investigate the transmission pattern of third-generation cephalosporin-resistant Enterobacterales in a NICU setting. This monocentric observational cohort study in a tertiary NICU in Heidelberg, Germany, enrolled all hospitalized neonates screened for cephalosporin-resistant Enterobacterales. Data were collected from 1 January 2018 to 31 December 2021. Weekly screening by rectal swabs for colonization with third-generation cephalosporin-resistant Enterobacterales was performed for all newborns until discharge. Whole-genome sequencing was performed for molecular characterization and transmission analysis. In total, 1,287 newborns were enrolled. The median length of stay was 20 (range 1–250) days. Eighy-eight infants (6.8%) were colonized with third-generation cephalosporin-resistant Enterobacterales. Low birth weight [<1500 g (adjusted odds ratio, 5.1; 95% CI 2.2–11.5; P < 0.001)] and longer hospitalization [per 30 days (adjusted odds ratio, 1.7; 95% CI 1.5–2.0; P < 0.001)] were associated with colonization or infection with drug-resistant Enterobacterales in a multivariate analysis. Enterobacter cloacae complex was the most prevalent third-generation cephalosporin-resistant Enterobacterales detected, 64.8% (59 of 91). Whole-genome sequencing, performed for the available 85 of 91 isolates, indicated 12 transmission clusters involving 37 patients. This cohort study suggests that transmissions of third-generation cephalosporin-resistant Enterobacterales in newborns occur frequently in a non-outbreak NICU setting, highlighting the importance of surveillance and preventive measures in this vulnerable patient group.